Buildings on Kongsbakken, near Parkgata in Tromsø,Norway - Campbell, Sandy (2024)
These buildings were across the road from Kings Park in Tromsø, Norway. The building in the foreground is older. It has orange exterior paneling and a peaked grey slate roof. It also has a narrow black on white banner that reads, "It's never too late to be a rock star." It also has two types of windows - vertical sash-type windows and diamond shaped feature windows. The building to the right is painted in three sections, white to the right, dark gold and pale yellow. The middle section has a rooftop patio. The building in the background is a modern apartment style building with a flat roof, rectangular windows and balconies.